2006
DOI: 10.1002/bit.20739
|View full text |Cite
|
Sign up to set email alerts
|

Effects of terpenoid precursor feeding on Catharanthus roseus hairy roots over‐expressing the alpha or the alpha and beta subunits of anthranilate synthase

Abstract: Among the pharmacologically important terpenoid indole alkaloids produced by Catharanthus roseus are the anti-cancer drugs vinblastine and vincristine. These two drugs are produced in small yields within the plant, which makes them expensive to produce commercially. Metabolic engineering has focused on increasing flux through this pathway by various means such as elicitation, precursor feeding, and introduction of genes encoding specific metabolic enzymes into the plant. Recently in our lab, a feedback-resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…The parallel cultivation of the ASab-1 line starting at 2.25 years after liquid adaptation and the stabilized metabolite profile from 2-5 years provides additional evidence that the line has become stable and is insensitive to differences in sub-culturing techniques. The increase in enzyme activity reported at Peebles et al, 2005Peebles et al, , 2006 5 years may explain why there is an observed change in metabolite levels over the first 2 years (Figs. 3 and 4).…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…The parallel cultivation of the ASab-1 line starting at 2.25 years after liquid adaptation and the stabilized metabolite profile from 2-5 years provides additional evidence that the line has become stable and is insensitive to differences in sub-culturing techniques. The increase in enzyme activity reported at Peebles et al, 2005Peebles et al, , 2006 5 years may explain why there is an observed change in metabolite levels over the first 2 years (Figs. 3 and 4).…”
Section: Resultsmentioning
confidence: 85%
“…At this point, a mixture of hairy roots containing different backgrounds may still exist. Over time as the five best growing hairy root tips are chosen for Peebles et al, 2005Peebles et al, , 2006 sub-culturing, we maybe selecting for a faster growing, more homogeneous culture. We are currently using a modified procedure in which each selection is based on a single root tip from the infected plant.…”
Section: Resultsmentioning
confidence: 99%
“…The high K m values for both loganic acid and AdoMet suggest that the catalytic activity of LAMT may be limiting the production of terpenoid component of MIA biosynthesis in C. roseus (Peebles et al, 2006).…”
Section: Kinetic Analyses and Substrate Specificity Studies With Rlammentioning
confidence: 99%
“…The induced TDC line showed no significant increase in tryptamine level but 129% increase in serpentine production, whereas TDC-ASa line showed 6-fold increase in tryptamine level but no increase in serpentine production (Hughes et al 2004b). Secologanin biosynthesis limitation in such transgenic hairy roots was confirmed (Peebles et al 2006). In feeding 1-deoxy-D-xylulose to ASa-overexpressing hairy root line, an increase of 125% in hoerhammericine was observed, while loganin feeding increased catharanthine by 45%.…”
Section: Manipulating Biosynthetic Genesmentioning
confidence: 68%